Initiation and regulation of iron economy in Arabidopsis thaliana chloroplasts - Kroh, Gretchen Elizabeth, author; Pilon, Marinus, advisor; Reddy, Anireddy, committee member; Bush, Daniel, committee member; Bedinger, Patricia, committee member; Argueso, Cristiana, committee member (Colorado State University. Libraries, 2020)
Iron (Fe) is biologically important for all organisms because of its role as a protein cofactor which provides redox and catalytic functions. Fe cofactors come in 3 different forms (Fe-S clusters, heme, and non-heme Fe). Plants have a stronger requirement for Fe than non-photosynthetic organisms because the chloroplast has a high demand for Fe. Plants are commonly Fe deficient because soil Fe is typically found in the non-bioavailable, ferric (Fe3+) form, which limits plant growth in natural and agricultural settings. When grown on soils where Fe availability is low, plants can increase Fe uptake and use Fe more efficiently. The leaf response to Fe limitation in the model plant, Arabidopsis thaliana, is the topic of my dissertation. As a major contribution to a larger study, I first characterized the transcriptional response for specific leaf genes to Fe deficiency in the leaf and found that transcripts for abundant chloroplast Fe proteins were down-regulated, suggesting an Fe economy response. Specifically, photosynthetic electron transport and chloroplast Fe-S assembly were targeted for down-regulation. Fe deficiency affects photosynthesis and chloroplast Fe protein expression. I characterized a photosynthesis mutant and found that the regulation of Fe protein expression is maintained, suggesting that loss of electron transport does not trigger down-regulation of Fe protein expression. By using RNA-seq, I analyzed genome-wide transcriptomic changes to identify co-regulated transcripts early in the Fe economy response, including candidate transcription factors. The transcriptional responses in wild type Fe limited plants and a chloroplast Fe-S assembly mutant were independent of each other, suggesting that Fe-S assembly does not generate a signal to regulate chloroplast Fe proteins. The novel insights provided in this dissertation form a foundation for understanding how photosynthetic organisms cope with Fe limitation. From an applied perspective, the results of this dissertation open new avenues to minimize effects of Fe deficiency in agricultural settings.
Zip file contains supplementary table.
Keywords: Fe-S cluster; iron homeostasis; chloroplast; photosynthesis; Ferredoxin